The effects of the national agricultural input voucher scheme (NAIVS) on sustainable intensification of maize production in Tanzania. (28th March 2021) - Kim, Jongwoo; Mason, Nicole M.; Mather, David; Wu, Felicia
Abstract: African agricultural input subsidy programmes (ISPs) have primarily focused on conventional intensification: raising yields through increased use of inorganic fertiliser and improved seeds. Yet the yield effects from maize‐focused ISPs have been smaller than anticipated, due in part to poor maize yield response to inorganic fertiliser resulting from low soil organic matter or pH. Joint use of inorganic fertiliser with complementary soil fertility management practices—for example, organic fertiliser or maize‐legume intercropping—can contribute to more sustainable forms of agricultural intensification, while also improving yield response to inorganic fertiliser and the effectiveness of ISPs. We analyse the effects of Tanzania's ISP from 2008 to 2014, the National Agricultural Input Voucher Scheme (NAIVS), on use of these practices. Results from correlated random effects (CRE) multinomial logit (MNL) models suggest that NAIVS participation is associated with an 8–10 percentage point increase in the probabilities of inorganic fertiliser use alone and of joint use of inorganic fertiliser with organic fertiliser and/or maize‐legume intercropping on consistent maize‐growing households' maize plots. CRE fractional MNL results suggest similar associations for the proportion of households' total maize plots area under these practices. These results suggest that, in some cases, NAIVS may have contributed to sustainable intensification of maize production.